Nilai-Nilai Inklusivitas dalam Uslub Al-Qur'an: (Replikasi Model Pendidikan Islam Inklusif Bagi Penyandang Disabilitas) - imam, Imam Alfi; Halwati, Umi; Hidayat, Imam Ma’arif; Al Faozi, Mahfudz; Kuswantoro, Kuswantoro (Universitas Islam Negeri Mataram, Indonesia, 2025)
This research aims to identify the values of inclusivity in the Qur'an and replicate it as an inclusive Islamic education model for people with disabilities. A qualitative approach is used with text analysis techniques on Qur'anic verses, hadiths, as well as Islamic and educational literature. Data were obtained from books, scientific journals, and relevant documents, which were then analyzed through thematic categorization and triangulation of experts' views. This study found that the uslub ‘ilmi, adabi, and khithabi in the Qur'an each contain the principles of equality, respect for physical diversity, social justice, and a call for collaboration that supports the creation of a disability-friendly education system. The results of this study show that the values of inclusivity in the Qur'an have strong relevance to the principles of modern inclusive education, such as accessibility, non-discrimination, and curriculum adaptation. These findings provide a theoretical contribution in the form of a strong theological foundation for the development of inclusive education in the context of Islam, as well as practical implications for teachers, policymakers, and society at large in building an education system that is fair for all. This research also highlights the need for further empirical studies to test the effectiveness of the implementation of this model in the field, as well as encourage synergy between stakeholders in realizing truly inclusive education.